Mixed farming and yams - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Nkosu Ephraim, a plant health specialist from Cameroon, describes land preparation methods, timing of weed control, and limitations that apply to herbicides and animal traction.